The prognostic significance of inflammation-immunity-nutrition score on postoperative survival and recurrence in hepatocellular carcinoma patients - Liang, Yuxin; Zhang, Zilong; Zhong, Deyuan; Lai, Chunyou; Dai, Zonglin; Zou, Haibo; Feng, Tianhang; Shang, Jin; Shi, Ying; Huang, Xiaolun (Frontiers in Oncology, 2022)
Background: Inflammation, immunity, and nutrition status play important roles in tumorigenesis, progression, and metastasis. This study aimed to evaluate the prognostic value of Inflammation-Immunity-Nutrition Score (IINS) for overall survival (OS) and recurrence-free survival (RFS) in patients with hepatocellular carcinoma (HCC) undergoing radical surgery. Methods: A total of 204 HCC patients were included in this retrospective study: 144 in the prediction model and 60 in the validation model. Multivariate Cox regression analysis was used to evaluate variables significant on univariate analysis. Kaplan-Meier survival curves were conducted to investigate the prognostic values of IINS, Alpha-fetoprotein (AFP) and IINS-AFP classification. The prognostic performances of all the potential prognostic factors were further compared by receiver operating characteristic (ROC) curve, and time-dependent ROC curve. The internal validation and external validation were used to ensure the credibility of this prediction model. Results: According to multivariate Cox regression analyses, the Barcelona Clinic Liver Cancer (BCLC) Stage , AFP, and IINS were independent prognostic factors for OS, and BCLC Stage, vascular invasion, and IINS were independent prognostic factors for RFS. High IINS group were associated with significantly worse OS and RFS compared with low IINS group. In terms of clinical prognosis, IINS-AFP classification was good in group I, moderate in group II, and poor in group III. Group I had a longer OS and RFS compared with group II and III. ROC analysis revealed that IINS-AFP classification had a better prognostic performance for OS and RFS than other predictors, excluding its slightly lower predictive power for RFS than IINS. The time-dependent ROC curves also showed that both IINS and IINS-AFP classification performed well in predicting OS for HCC patients. Furthermore, the internal validation and external validation proved that IINS had good predictive performance, strong internal validity and external applicability, and could be used to establish the prediction model. Conclusion: Inflammation-immunity-nutrition score could be a powerful clinical prognostic indicator in HCC patients undergoing radical surgery. Furthermore, IINS-AFP classification presents better prognostic performance than IINS or AFP alone, and might serve as a practical guidance to help patients adjust treatment and follow-up strategies to improve future outcomes.